Construction of a SSR-based genetic map and identification of QTLs for catechins content in tea plant (Camellia sinensis). - Jian-Qiang Ma; Ming-Zhe Yao; Chun-Lei Ma; Xin-Chao Wang; Ji-Qiang Jin; Xue-Min Wang; Liang Chen (PLoS ONE, 2014)
Catechins are the most important bioactive compounds in tea, and have been demonstrated to possess a wide variety of pharmacological activities. To characterize quantitative trait loci (QTLs) for catechins content in the tender shoots of tea plant, we constructed a moderately saturated genetic map using 406 simple sequence repeat (SSR) markers, based on a pseudo-testcross population of 183 individuals derived from an intraspecific cross of two Camellia sinensis varieties with diverse catechins composition. The map consisted of fifteen linkage groups (LGs), corresponding to the haploid chromosome number of tea plant (2n = 2x = 30). The total map length was 1,143.5 cM, with an average locus spacing of 2.9 cM. A total of 25 QTLs associated with catechins content were identified over two measurement years. Of these, nine stable QTLs were validated across years, and clustered into four main chromosome regions on LG03, LG11, LG12 and LG15. The population variability explained by each QTL was predominantly at moderate-to-high levels and ranged from 2.4% to 71.0%, with an average of 17.7%. The total number of QTL for each trait varied from four to eight, while the total population variability explained by all QTLs for a trait ranged between 38.4% and 79.7%. This is the first report on the identification of QTL for catechins content in tea plant. The results of this study provide a foundation for further cloning and functional characterization of catechin QTLs for utilization in improvement of tea plant.